2018
DOI: 10.2196/jmir.8868
|View full text |Cite
|
Sign up to set email alerts
|

Developing Embedded Taxonomy and Mining Patients’ Interests From Web-Based Physician Reviews: Mixed-Methods Approach

Abstract: BackgroundWeb-based physician reviews are invaluable gold mines that merit further investigation. Although many studies have explored the text information of physician reviews, very few have focused on developing a systematic topic taxonomy embedded in physician reviews. The first step toward mining physician reviews is to determine how the natural structure or dimensions is embedded in reviews. Therefore, it is relevant to develop the topic taxonomy rigorously and systematically.ObjectiveThis study aims to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Although involvement of family and friends is increasingly viewed as an important component of PCC [1,59-61], patients seldom expressed dissatisfaction with it in our research; apparently far less complained about the low participation of themselves. Compared with technical competence, which constituted a fundamental aspect of health care provision [23], interpersonal attributes of professionals were much more likely to be evaluated by patients; the potential implications of this are twofold: first, consistent with the study by Jia Li et al [26], patients’ needs have different hierarchy, which were firstly stated by Maslow [62], and second, patients have uninformed expectation—“patients are not capable or are reluctant to communicate their expectations” [61], which was validated by Rothenfluh and Schulz [63]. Although there were common concerns across different countries’ patients, variation existed in this study as well.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Although involvement of family and friends is increasingly viewed as an important component of PCC [1,59-61], patients seldom expressed dissatisfaction with it in our research; apparently far less complained about the low participation of themselves. Compared with technical competence, which constituted a fundamental aspect of health care provision [23], interpersonal attributes of professionals were much more likely to be evaluated by patients; the potential implications of this are twofold: first, consistent with the study by Jia Li et al [26], patients’ needs have different hierarchy, which were firstly stated by Maslow [62], and second, patients have uninformed expectation—“patients are not capable or are reluctant to communicate their expectations” [61], which was validated by Rothenfluh and Schulz [63]. Although there were common concerns across different countries’ patients, variation existed in this study as well.…”
Section: Discussionmentioning
confidence: 54%
“…Practices observed from the adverse event taxonomy proposed by Harrison et al [24], which facilitated the collection and aggregation of data to compare findings, identify priorities, and develop wide-reaching patient safety solutions, demonstrated the momentousness of a unified, agreed framework with standardized concepts and terms. Despite the large volume of work published in this domain (eg, the studies by Reader et al [25] and Li et al [26]), currently available taxonomies for analyzing online complaints made by patients often lack standardized themes, terminology, and underlying unifying theory, creating difficulties in making sense of data that cannot be used to compare against other services, organizations, or countries. An operational and rigorous framework that classifies complaints made by patients, containing standardized concepts with agreed definitions and preferred terminology and establishing the relationships between concepts based on an explicit and nonoverlapping domain ontology, is required [24].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the Bing Sentiment Dictionary [47] and the SODictionariesV1.11Spa2 [48] were used to analyze the content of the free text and obtain a description of the acceptance or rejection (polarity) [49] of the OR2-LMC treatment. Content analysis has been used previously in the health sciences to study medical and patient narratives [50,51]. Four phases were used progressively for the analysis of acceptance-rejection (polarity).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, given the variability in rating scales and domains across the PRW, the inclusion of multiple PRWs and systematic comparison is difficult. Novel methods of automated analysis of text reviews have been recently reported and may allow for a more comprehensive study of text-based patient reviews in the future [30,31].…”
Section: Discussionmentioning
confidence: 99%